Transformações da biopolítica e emergência da ecopolítica - Passetti, Edson (Ecopolítica, 2013)
As transformações da biopolítica sinalizam para a conformação da ecopolítica como governo do planeta. O presente artigo procura posicionar a emergência da ecopolítica, situando suas implicações com as decisões transterritoriais e a o desenvolvimento sustentável. Palavras-chave: biopolítica, ecopolítica, neoliberalismo, sociedade civil. Transformations of biopolitics and the emergence of ecopolitics Abstract: The transformations of biopolitics point out to the conformation of ecopolitics as government of the planet. The present article seeks to position the emergence of ecopolitics, situating its implications with transterritorial decisions and sustainable development. Keywords: biopolitics, ecopolitics, neoliberalism, civil society.